Ehrlichia Species in Dromedary Camels (Camelus dromedarius) and Ruminants from Somalia - Osman, Aamir M.; Hassan-Kadle, Ahmed A.; André, Marcos R. [UNESP]; Collere, Flávia C. M.; Córdova, Amir Salvador Alabí [UNESP]; Montiani-Ferreira, Fabiano; Vieira, Thállitha S. W. J.; Ibrahim, Abdalla M.; Yusuf, Abdulkarim A.; Machado, Rosangela Z. [UNESP]; Vieira, Rafael F. C. (MDPI, 2025)
Ehrlichioses, caused by Ehrlichia species, are tick-borne diseases (TBDs) that affect animals and humans worldwide. This study aimed to investigate the molecular occurrence of Ehrlichia spp. in 530 animals (155 Dromedary camels, 199 goats, 131 cattle, and 45 sheep) in the Benadir and Lower Shabelle regions of Somalia. Blood DNA samples were tested for PCR targeting dsb and sodB genes of Ehrlichia spp. and PCS20 and map1 genes of E. ruminantium. The obtained sequences were submitted for phylogenetic analyses. Ehrlichia spp. were detected in 26.4% (140/530) of animals by dsb-PCR, with the highest prevalence in dromedary camels (54.8%), followed by cattle (29.8%), goats (7.0%), and sheep (4.4%). Dromedary camels, cattle, and goats had significantly higher infection odds compared to sheep (p < 0.05). Among dsb-PCR-positive samples, 76.9% (30/39) of cattle tested sodB-positive, while other species were negative. E. ruminantium was detected in 13.7% (18/131) of cattle by pCS20-PCR, but none were positive for the map1 gene. Phylogenetic analysis confirmed E. minasensis in camels, sheep, and goats and E. ruminantium in cattle, marking the first molecular evidence of E. minasensis in dromedary camels, sheep, and goats globally, and E. ruminantium in cattle from Somalia. These findings emphasize the need for further research on its economic and public health impact.
Keywords: Ehrlichia minasensis; Ehrlichia ruminantium; ehrlichiosis; heartwater; Somalia; sub-Saharan Africa; tick-borne diseases